Selective fluorometric detection of F− and Zn(ii) ions by a N, O coordinating sensor and naked eye detection of Cu(ii) ions in mixed-aqueous solution1. Issue 56 (19th June 2015) - Hens, Amar; Rajak, Kajal Krishna
<x xml:space="preserve">Abstract</x> A N, O coordinating sensor fluorogenically detects fluoride anions (λex = 330 nm, λem = 450 nm) with blue emission and Zn(ii) ions with green emission (λex = 405 nm, λem = 515 nm) as well as colorimetrically detecting copper ions.